MANAJEMEN PENDIDIKAN ANAK USIA DINI DALAM PERSPEKTIF AL-QUR’AN - Sabaruddin MZ (LPPM Sekolah Tinggi Agama Islamm (STAI) Fatahillah Serpong, Tangerang Selatan-Banten, Indonesia, 2020)
This research is a library research, data collection is done by collecting primary and secondary data sources. In analyzing the data that has been collected the author uses data analysis (content analysis). Early childhood education is a preschool education which contains special activities and is packaged in play activities and planning of learning of early childhood education must always adjust to the level of development of preschool children. So from the success of early childhood education there needs to be good management, methods, and also good material. In this case, the Qur'an as a guide to human life explains about early childhood education, starting from its management, methods, and material